Sustainable conversion of waste biomass using hydrothermal carbonization method - Jelena V. Milojković; Časlav M. Lačnjevac (Zaštita Materijala, 2015)
Hydrothermal carbonization represents a process for converting a wet organic material at elevated temperature and pressure in hydro char, coal-like product. The resulting hydro char, depending on the nature of biomass, can be used as a substitute for fossil coal, adsorbent of various pollutants, soil fertility supplement and others. This paper provides insight into the reaction mechanisms, as well as the influence of process parameters. It also highlighted the importance and advantage of the process of hydrothermal carbonization of biomass compared to traditional methods of conversion, as well as the actual implementation of the product.